Implementasi Kurikulum Merdeka pada Mata Pelajaran IPAS - Wati, Ni Nyoman Kurnia (STAHN Mpu Kuturan Singaraja, 2023)
The gap between expectations and implementation of the curriculum, especially in science subjects, causes the need for a study of its implementation. IPAs in the Merdeka curriculum are expected to be carried out in an integrated manner, integrated between the content of science and social studies. This research is a mixed methods research or a mixture of quantitative and descriptive. The sample of this study were teachers in class IV cluster III, Buleleng District. Data was collected using interview sheets and direct observation of teachers in cluster III, Buleleng District. Data analysis uses descriptive, namely presenting research results based on qualitative data. Based on the literature review, interviews, and also observations that have been made, it can be concluded that the implementation of the independent learning curriculum, especially the science subject in elementary school cluster III, Buleleng sub-district, has been carried out well. It's just that the teacher must further develop his abilities so that he can create innovations in learning. It is hoped that the curriculum teachers will not be replaced continuously, but rather refinement of what already exists. In addition to being equipped with training, teachers should not be burdened with a lot of teaching administration.